2016
DOI: 10.1016/j.neuron.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A Primary Role for Nucleus Accumbens and Related Limbic Network in Vocal Tics

Abstract: Inappropriate vocal expressions, e.g., vocal tics in Tourette syndrome, severely impact quality of life. Neural mechanisms underlying vocal tics remain unexplored because no established animal model representing the condition exists. We report that unilateral disinhibition of the nucleus accumbens (NAc) generates vocal tics in monkeys. Whole-brain PET imaging identified prominent, bilateral limbic cortico-subcortical activation. Local field potentials (LFPs) developed abnormal spikes in the NAc and the anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…Unlike basal ganglia diseases which are associated with impairment of involuntary movement, cerebellar disorders are associated with failing of voluntary movement. The role of the cerebellum in the pathophysiology of GTS was most recently supported in an investigation in which vocal and motor tics were induced by focal disruption in ventral and motor striatum, respectively (McCairn et al 2016). Interestingly, metabolic observations in those experiments also implicated the hippocampus and amygdala, although the other subcortical nuclei of the CBGTC were not associated.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 96%
See 1 more Smart Citation
“…Unlike basal ganglia diseases which are associated with impairment of involuntary movement, cerebellar disorders are associated with failing of voluntary movement. The role of the cerebellum in the pathophysiology of GTS was most recently supported in an investigation in which vocal and motor tics were induced by focal disruption in ventral and motor striatum, respectively (McCairn et al 2016). Interestingly, metabolic observations in those experiments also implicated the hippocampus and amygdala, although the other subcortical nuclei of the CBGTC were not associated.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 96%
“…An investigation which also employed [ 15 O] H 2 O PET in which vocal and motor tics were induced in non-human primates reported a much smaller network with different activated brain regions (McCairn et al 2016). Injection of the GABA antagonist bicuculline into the NA or dorsolateral sensorimotor putamen produced repetitive complex vocalizations or motor tics in the orofacial and/or the arm region, respectively.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
“…Over the past two decades, DBS has been used as a promising treatment option for medication refractory and severely affected patients with TS 6–8. Evidence from neuroimaging,9–11 stereotactic lesions12–14 and animal models15–17 have collectively demonstrated that the thalamo-striatal-cortical circuit18 is involved in the pathophysiology of TS. Based on these findings, thalamic and pallidal nuclei in the circuits have been selected as DBS targets for the treatment of TS.…”
Section: Introductionmentioning
confidence: 99%
“…A face-valid animal model of tics has been a very important but elusive goal 33 . McCairn and colleagues have now published their important work characterizing a nonhuman primate tic model 34 . Temporary unilateral disinhibition of the nucleus accumbens (NA)—the ventral, more limbic-connected part of the striatum—produces vocalizations in monkeys that resemble vocal tics in human patients.…”
Section: Resultsmentioning
confidence: 99%